Handbook of religion and the authority of science - Hammer, Olav.; Lewis, James R. (Brill Handbooks on Contemporary Religion, 2011)
There has been a significant but little-noticed aspect of the interface between science and religion, namely the widespread tendency of religions to appeal to science in support of their truth claims. Though the appeal to science is most evident in more recent religions like Christian Science and Scientology, no major faith tradition is exempt from this pattern. Members of almost every religion desire to see their 'truths' supported by the authority of science - especially in the midst of the present historical period, when all of the comforting old certainties seem problematic and threatened. The present collection examines this pattern in a wide variety of different religions and spiritual movements, and demonstrates the many different ways in which religions appeal to the authority of science. The result is a wide-ranging and uniquely compelling study of how religions adapt their message to one of the major challenges presented by the contemporary world.